Global outlook : high intermediate reading - Bushell, Brenda; Dyer, Brenda (Boston : McGraw Hill, 2003)
"Global outlook is a two-book series designed to introduce learners to the basic reading skills required for fluent, accurate reading in English."--P. [4] of cover.
1. The global village -- 2. Travel -- 3. Biodiversity -- 4. Love -- 5. Time -- 6. Green Business -- 7. Beauty -- 8. Wireless technology -- 9. Media and culture -- 10. Development -- 11. Cloning -- 12. Future worlds
Keywords: English language -- Textbooks for foreign speakers; English language -- Study and teaching -- Foreign speakers; Readers (Adult); Readers for new literates; Readers -- Civilization; Readers -- Environmental protection; Readers -- Globalization; Reading comprehension -- Problems, exercises, etc